Fracture Processes in Steel Fibre Reinforced Concrete: Influence of fibre and matrix relationship on the fracture processes - Htut, Trevor; Foster, S. (VDM Verlag Dr. Muller, 2011)
Cementitious materials are brittle and have an inherent weakness in resisting in tension. Fibre reinforcement is an effective mean of enhancing the fracture characteristics of concrete. An increase in fibre volume concentration can have an adverse effect on the tensile performance of a SFRC when very high strength, end-hooked fibres are used in a matrix of moderate strength. The study showed that an increase in fibre volume concentration can lead to a decreased in the proportion of end-hooked fibres straightening through the end-hook. In this case, failure of the matrix surrounding the hook follows and significantly influences the behaviour. A relationship between fibre and matrix mechanical properties was developed and the result supports the findings obtained from the tests conducted in this study. X-ray imaging was undertaken on dog-bone specimens under load. The tests were used to map the cracks around and through the fibre and a statistical model was developed to determine fibre distribution.